The Prevalence of Traditional Malpractice during Pregnancy, Child Birth, and Postnatal Period among Women of Childbearing Age in Meshenti Town, 2016 - Gedamu, Haileyesus; Tsegaw, Adane; Debebe, Etsubdink (International Journal of Reproductive Medicine, 2018)
Background. Cultural practices, beliefs, and taboos are often implicated in determining the care received by mothers during pregnancy and child birth which is an important determinant of maternal mortality. Objective. To assess prevalence of cultural malpractice during pregnancy, child birth, and postnatal period among women of childbearing age in Meshenti town, Amhara region, northwest Ethiopia, in 2016. Methods. Community based cross-sectional study was conducted among women of reproductive age group interviewed during the study period from May 10 to June 17, 2016. Total sample size was 318 women of reproductive age group. Systematic sampling technique was conducted. Result. Overall, 50.9% of the respondents had cultural malpractices during their pregnancy. Out of 318 women, 62 (19.5%) practiced nutrition taboo, 78 (24.5%) practiced abdominal massage, 87 (29.7%) delivered their babies at home, 96 (32.8%) avoided colostrums, 132 (45.2%) washed their baby before 24 hr after delivery, and 6 (6.9%) cut the cord by unclean blade. Conclusion and Recommendation. The findings of this study show that different traditional malpractice during perinatal period is still persisting in spite of modern developments in the world. Health education and promoting formal female education are important to decrease or avoid these cultural malpractices.